Robotic bronchoscopy for peripheral pulmonary lesions: a convergence of technologies. Issue 4 (July 2021) - Lin, Julie; Ost, David E.
Abstract : Purpose of review: Robotic bronchoscopy is the newest advanced diagnostic bronchoscopy technology for biopsying peripheral pulmonary lesions; sensitivity for malignancy is currently suboptimal using modalities, such as radial endobronchial ultrasound or electromagnetic navigational bronchoscopy. We review the pitfalls of prior methods and the technological advancements with robotic bronchoscopy. Recent findings: The contributors to reduced diagnostic sensitivity with current approaches include limitations in: navigation to the target, confirmation once the target is reached, and tissue acquisition. CT to body divergence with virtual reality methods, such as with electromagnetic navigation, potential false-positive confirmation with radial endobronchial ultrasound because of intraprocedural induced atelectasis, and lack of bronchoscopic and instrument maneuverability are all limitations to improving sensitivity. Robotic bronchoscopy enhances navigation through target pathway selection, allows for further reach in the distal airways, and improves tissue acquisition with more flexible and maneuverable biopsy instruments but lacks a high-fidelity target confirmation system. Summary: Robotic bronchoscopy shows promise in biopsying peripheral lesions. Current published studies focus on diagnostic yield with robotic bronchoscopy. Future studies with long-term follow-up will be needed to assess diagnostic sensitivity for lung cancer and if robotic bronchoscopy is superior to other advanced diagnostic bronchoscopic techniques for peripheral pulmonary lesions.